Effect of Hydrophile-Lipophile Balance (HLB) of Mixed Surfactants on In-Vitro Release Profile of Ibuprofen from Semi-Synthetic Suppository Bases (Nigerian Journal of Pharmaceutical Research, 2021)
Background: The emphasis on the use of surfactants in enhancing drug release from fatty suppository bases has always been on the concentration and type of surfactants. However, the Hydrophile-Lipophile Balance (HLB) of the surfactants added can be of significant effect.Objective: The study aimed at evaluating the effect of HLB of the incorporated mixed surfactants on the physical and release properties of Ibuprofen suppositories formulated with semi-synthetic fatty bases.Methodology: The preparations were carried out using 1 g mould. Ibuprofen suppositories, each containing 200 mg of Ibuprofen with semi-synthetic fatty bases (Witepsol® H15, Suppocire® CM), were prepared by fusion method. Mixed surfactants (Span® 80 and Tween® 80) were added at 4 %w/w in varied ratios to give HLB values of 4.3 to 15.0. The physical properties and release profile of the suppositories were evaluated using established procedures.Results: The physical properties of the suppositories met the standard specified in the BP. Addition of mixed surfactants greatly influenced the release of the Ibuprofen from the formulations with optimum release at lipophilic HLB (4.3) and hydrophilic HLB (12.0) for formulations in Suppocire® CM and Witepsol® H15, respectively. The release parameters majorly fitted into Higuchi’s model. The release mechanism was non-Fickian and Fickian for formulations in Suppocire® CM and Witepsol® H15, respectively.Conclusion: The variations observed in the release profiles of Ibuprofen from the suppository bases indicate that HLB value of mixed surfactants can be employed in modifying drug release from semi-synthetic fatty bases